2013
DOI: 10.1117/1.jbo.18.2.027007
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the cerebral metabolic rate of oxygen by combining diffuse correlation spectroscopy and time-resolved near-infrared spectroscopy

Abstract: Preterm infants are highly susceptible to ischemic brain injury; consequently, continuous bedside monitoring to detect ischemia before irreversible damage occurs would improve patient outcome. In addition to monitoring cerebral blood flow (CBF), assessing the cerebral metabolic rate of oxygen (CMRO2) would be beneficial considering that metabolic thresholds can be used to evaluate tissue viability. The purpose of this study was to demonstrate that changes in absolute CMRO2 could be measured by combining diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 63 publications
2
54
1
Order By: Relevance
“…The approach taken by Baker et al can be combined with the multi-layered model presented in this study to isolate cerebral signals detected by DCS when estimating extracerebral tissue thickness by imaging methods is unavailable. Future work will implement a multi-layered DCS/TR-NIRS hybrid to demonstrate a means of quantifying the cerebral metabolic rate of oxygen in adults [14,50].…”
Section: Resultsmentioning
confidence: 99%
“…The approach taken by Baker et al can be combined with the multi-layered model presented in this study to isolate cerebral signals detected by DCS when estimating extracerebral tissue thickness by imaging methods is unavailable. Future work will implement a multi-layered DCS/TR-NIRS hybrid to demonstrate a means of quantifying the cerebral metabolic rate of oxygen in adults [14,50].…”
Section: Resultsmentioning
confidence: 99%
“…For example, blood flow can be measured by manipulating arterial oxygenation saturation or injecting a light-absorbing contrast agent [4][5][6]; however, these techniques only enable single time-point measurements. An alternative approach that provides continuous blood flow monitoring is diffuse correlation spectroscopy (DCS) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the current lack of adequate methods for RA treatment monitoring, this technique could play a significant role in the management of this debilitating disease. Note that there are other optical techniques-diffuse correlation spectroscopy (DCS) and changes in Hb and HbO 2 following venous occlusion-that can noninvasively measure deep tissue perfusion [54][55][56][57]. However, while it has been shown that the venous occlusion method can quantify blood flow in muscle [57], its ability to quantify joint perfusion has yet to be tested.…”
Section: Discussionmentioning
confidence: 99%